The Economic Empowerment of the Ummah on the Basis of Productive Waqf in West Sumatra, Indonesia - Rozalinda Syamsir (UIN Sunan Gunung Djati Bandung, 2015)
West Sumatra owns a very prospective waqf asset. Yet, in general it has been managed traditionally. Only some counties have already implemented productive waqf management. This study examines the productive waqf management roles in empowering the ummah economy in West Sumatra including the supporting and inhibiting factors in implementing the productive waqf management in this province. This work is a qualitative descriptive study which verbalizes and analyzes the data holistically. The data of this research are collected from interviews and written documents. The purpose of this research is to analyze the role of productive waqf in empowering the ummah’s economy in West Sumatra as well as to elaborate the supporting and inhibiting factors in developing the waqf productive in West Sumatra. Business facilities provided by the waqf management institutions give communities more chances to get employed or to expand their businesses and gain more profits so increase their living standards as well. As a whole the waqf management in West Sumatra has gone well and got supported from most community members. The only obstacle is limited cash waqf so make it rather difficult to expand the waqf assets. Therefore in order to make the ummah economic empowerment on the basis of productive waqf becomes more effective, it is suggested that the waqf management institutions introduce a money waqf movement.